دور الصداقة في حياة الشباب الجامعي "دراسة ميدانية على عينة من طلبة كليتي التربية والعلوم في جامعة دمشق" - الشمّاس, عيسى; ياسين, بسيم (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت هذه الدراسة إلى التدليل على دور الصداقة في حياة الشباب الجامعي لدى عينة من طلبة جامعة دمشق، وإلى معرفة أثر متغير الجنس والبيئة الاجتماعية في تحديد الفروقات في هذا الدور. تكونت عينة الدراسة من (254) طالباً وطالبة من طلبة السنة الأولى في الكليات التي تمّ تطبيق الدراسة فيها، واعتمد الباحث الاستبانة كأداة لتحقيق هدف الدراسة. وتوصلت الدراسة إلى النتائج الآتية: _ وجود فروق ذات دلالة إحصائية، عند مستوى الدلالة (0.05) بين متوسطات إجابات طلبة جامعة دمشق المتعلقة بتحديدهم لوظيفة الصداقة الاجتماعية والأدوار المرتبطة به وفقاً لكل متغير من متغيرات البحث (الجنس، البيئة الاجتماعية). _ وجود فروق ذات دلالة إحصائية، عند مستوى الدلالة (0.05) بين متوسطات إجابات طلبة جامعة دمشق المتعلقة بتحديدهم لوظيفة الصداقة النفسية والأدوار المرتبطة به بحسب متغير جنس الطلبة. _ وجود فروق ذات دلالة إحصائية، عند مستوى الدلالة (0.05) بين متوسطات إجابات طلبة جامعة دمشق المتعلقة بتحديدهم لوظيفة الصداقة المعرفية والأدوار المرتبطة بذلك التحديد تبعاً لمتغير جنس الطلبة. The study aimed to identify the role of friendship in the lives of university youth، and to know the impact of the variables sex and the social environment in determining the differences in the role. The study sample consisted of 254 first year students in the college in which the study was done. the researcher has adopted the use of a questionnaire as a tool to achieve the goal of the study. The study found the following results: 1. there are differences of statistical significance at rate 0.05 among average replies of Damascus University students، regarding their identifying with the Friendship social function and the roles associated with it according to the according to the variant of the students' gender, social environment. 2. There are differences of statistically significance at rate 0.05 among average replies of Damascus University students، regarding their identifying with the Friendship and mental function and the roles associated with it، according to the students’ gender variable. 3. There are differences of statistical significance at rate 0.05 among average replies of Damascus University students regarding their identifying with the Friendship cognitive function and the roles associated with it، according to the students’ gender variable.